ANALISIS PAJAK PENGHASILAN PASAL 23 ATAS JASA FREIGHT FOWARDING PADA PT. ENERGY LOGISTICS CABANG MANADO - Akerina, Enrico; Tinangon, Jantje J.; Mawikere, Lidia M. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
This study discusses the Income Tax Article 23 withholding treatment of a series of transactions conducted by the Freight forwarding . the authors conducted an analysis of the suitability of the practice of withholding tax by Act No. 36 of 2008. Results of this analysis will eventually be recommended to the PT . Energy Logistics so as not to make a mistake in the determination of article 23, particularly in Freight forwarding service activities, since not all of these activities subject to Income Tax Article 23. At the PER178/PJ/2006, stated that the services of Freight forwarding is the object of withholding income tax article 23, while according to the latest regulations PER70/PJ/2007, Freight forwarding services not subject to withholding income tax article 23, but there are some services that a positive list of Income Tax Article 23 refers to the object on which PER-70/PJ/2007 such as storage services, brokerage services, packing services, pest control services are mostly done by Freight forwarding. This gives rise to multiple interpretations for implementers and users Freight forwarding services over a series of Freight forwarding services because of the uncertainty between the two rules.Keywords : Object list Positive article 23 of Income Tax, Freight Forwarding